Effects Of Mixed Asphals With Feldspar Filler Modification On Oil Asphals - Latifun Latifun; Antonius Antonius (International Conference on Coastal and Delta Areas, 2017)
Each composite material in a pavement mixture gives different variations of characteristics and performance, therefore it is still necessary to test the variations of the material to find the suitability of the use, so that by testing it can contribute information about the use of materials that can be used as an alternative in reference to choosing a replacement material This study aims to determine the characteristics of marshall using asphalt binder modified polymer AC 50/70 by using the material of feldspar stone ash, in terms of Marshall stability, flow VF, VIM (Void in Mix), VIM (Void in Bix) VMA (Void in Mineral Aggregate), MQ (Marshall Quotient), and. Density, This research uses hot mixed asphalt test (Hot Mix) with Marshall method. The asphalt content used was 4%, 4.5%, 5%; 5.5%; 6%; 6.5%; and 7% with each variant made 5 specimen. Implementation of the research was conducted at Civil Engineering Laboratory Faculty of Engineering, Islamic University of Sultan Agung Semarang. Implementation stages include aggregate examination (fine aggregate and coarse aggregate), filler examination, manufacture of asphalt concrete mix test and test using Marshall method. Keywords: Asphalt mixture, feldspar, filler, Asphalt oil